Two new spongian diterpene derivatives from the aquaculture sponge Spongia officinalis Linnaeus, 1759. Issue 2 (17th January 2023) - Jin, Tianyun; Li, Pinglin; Wang, Cili; Tang, Xuli; Yv, Xiaoli; Li, Kai; Luo, Lianzhong; Ou, Huilong; Li, Guoqiang
Abstract: 2 β, 3 α, 19-Triacetoxy-17-hydroxyspongia-13(16), 14-diene (1 ), a novel acetoxy diterpenoid, and 18-nor-2, 17-hydroxyspongia-1, 4, 13(16), 14-quaien-3-one (2 ), belonging to the rare 18-nor-spongian carbon skeleton, together with six related known metabolites (3 ‒8 ), were isolated from the aquaculture Spongia officinalis Linnaeus, 1759. Their structures were elucidated by comprehensive spectroscopic analysis, quantum chemical calculation of NMR parameters, and electronic circular dichroism (ECD). Compounds 3, 4, and 5 exhibited moderate inhibition against STAT3/NF- κ B, HIF-1, Wnt signalling pathways. Compounds 1, 3, and 5 showed cytotoxicity activities against K562 cell line with IC50 values of 7.3, 3.5, and 6.4 μ M, respectively. Graphical Abstract: UF0001